Restrictions towards Community Activities (PPKM) to Overcome the COVID-19 Pandemic in the Eyes of STIAMI Students and Lecturers: A Mass Communication Study - Abidin, Nadiah; Zahran, Wahidin Septa; Widyastuti, Trie Andari Ratna; Vitisia, Vita; Saktisyahputra, Saktisyahputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
To overcome the COVID-19 pandemic, the Indonesian government decided to implement a regulation known as the Restrictions towards Community Activities (PPKM). Since its inception, PPKM has been extended fourteen times. Observing the trend, it is interesting to find out how higher education students and lecturers perceive the regulation after gaining information from varied mass communication channels. Therefore, this research is aimed to identify perceptions regarding PPKM among students and lecturers. It used qualitative research with a phenomenology approach, involving 104 STIAMI students and 26 lecturers based in Jakarta, Bekasi, and Depok. According to the results, more than a half of the students and lecturers found information to be sufficient from mass communication channels and decided to support the program if continued in the future. They are, however, urging the government to conduct significant changes that would ensure the social and economic lives of Indonesian citizens remain well.